Inhibition studies of the protozoan α-carbonic anhydrase from Trypanosoma cruzi with phenols - Alessandro Bonardi; Seppo Parkkila; Claudiu T. Supuran (Taylor & Francis Group, 2022)
The α-class carbonic anhydrase (CA, EC 4.2.1.1) from the protozoan pathogen Trypanosoma cruzi, TcCA, was investigated earlier for its inhibition with anions, sulphonamides, thiols and hydroxamates, well-known classes of CA inhibitors (CAIs). Here we present the first inhibition study of this enzyme with phenols, which possess a diverse CA inhibition mechanism compared to the previously investigated compounds, which are all zinc binders. Indeed, phenols are known to anchor to the zinc coordinated water molecule within the enzyme active site. In a series of 22 diversely substituted phenols, the best inhibitors were simple phenol, pyrocatechol, salicylic acid, 3,5-difluorophenol, 3,4-dihydroxy-benzoic acid, 3,6- dihydroxy-benzoic acid, caffeic acid and its des-hydroxy analog, with KIs of 1.8 − 7.3 µM. The least effective TcCA inhibitor was 3-chloro-4-amino-phenol (KI of 47.9 µM). Although it is not yet clear whether TcCA can be considered as an anti-Chagas disease drug target, as no animal model for investigating the antiprotozoan effects is available so far, finding effective in vitro inhibitors may be a first relevant step towards new antiprotozoal agents.